Pion, kaon, and (anti)proton production in U+U collisions at √sNN=193 GeV measured with the STAR detector - Abdallah, Mohamed Samy; Deppner, Ingo Martin; Söhngen, Yannick; Weidenkaff, Philipp (Physical review, 2023)
We present the first measurements of transverse momentum spectra of π±, K±, p(¯p) at midrapidity (|y|<0.1) in U+U collisions at √sNN= 193 GeV with the STAR detector at the Relativistic Heavy Ion Collider (RHIC). The centrality dependence of particle yields, average transverse momenta, particle ratios and kinetic freeze-out parameters are discussed. The results are compared with the published results from Au+Au collisions at √sNN= 200 GeV in STAR. The results are also compared to those from A Multi-Phase Transport (ampt) model.